Integrating Artificial Intelligence and Canva as Instructional Media in Elementary Education: A Field Study at SDN 069 Mompang Julu, Indonesia - Siti Sartimah; Yustika Aulia Dalimunthe (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the integration of Artificial Intelligence (AI) and Canva as instructional media in elementary school learning, particularly at SDN 069 Mompang Julu, Indonesia. The research employed a qualitative approach with a field study design. The research subjects consisted of elementary school teachers and students, while data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the use of AI and Canva assists teachers in designing more creative, visual, and efficient learning media, as well as increasing students’ motivation and engagement in the learning process. The discussion reveals that the integration of these technologies creates a more adaptive and engaging learning experience; however, it still faces challenges related to teachers’ digital competence and technological infrastructure. The study concludes that the integration of AI and Canva has strong potential to improve the quality of elementary education when supported by continuous teacher training and adequate technological facilities.